PENDAMPINGAN IMPLEMENTASI KURIKULUM 2013 MELALUI SULASTRI DI SMPN 15 BANJARMASIN - Arbainah Arbainah (Vidya Karya, 2020)
The 2013 Curriculum Implementation assistance activity is an essential first step to accelerate understanding and skills in implementing the curriculum. To maintain and improve the continuity, performance, and implementation of the 2013 curriculum in each education unit, a study was carried out to implement the 2013 curriculum through "Sulastri" at SMPN 15 Banjarmasin. This mentoring program was carried out as a strengthening in understanding the concept of the 2013 curriculum.Cycle I Planning consists of a) determining teacher data to be given Sulatri, b) preparing observation sheets in the form of Sulastri instruments, namely teaching and learning administrative supervision instruments and classroom supervision instruments, c) holding initial meetings with teachers who would be given Sulastri for information and scheduling for each teacher, d) delivering the supervision instrument to each teacher who would be supervised, e) explaining the assessment that the teacher needs to know contained in the supervision instrument, f) explaining the main components of learning administration tools collected before the implementation of classroom supervision. In cycle II, it was carried out if the results of cycle I were considered unsuccessful or the indicators of research success had not reached the predetermined target.From the implementation of the first cycle, which was applied where Sulastri was carried out on 14 teachers, there had been an increase in the quality of performance even though it was still in the early stages, and the results were as follows: 1) The results of the supervision of learning administration (teaching and learning administration), the achievement of good and very good performance quality were 41.67%, 2) The results of classroom supervision, the achievement of good and excellent performance quality were 58.33%. Implementation of cycle II, which was re-implemented, was carried out by Sulastri activities. Against 14 teachers as research subjects, there has been a very significant increase in the quality of performance, namely: 1) The results of the supervision of the learning administration (lesson planning) have achieved a good and very good quality of performance by 100%. 2) The results of classroom supervision (implementation of learning), the achievement of good and excellent quality performance was 92.85%.With continuous supervision that is applied to all teachers at least once a year, teachers in carrying out their duties properly because they feel that there is supervision/control as well as coaching, so that it can be used to measure the quality of teacher performance on professional competencies both in the aspects of learning planning and implementation of learning. Implementing an integrated classroom supervision strategy abbreviated as Sulastri, and through Sulastri, it turns out to motivate the growth of willingness and ability to change, which leads to changes in improving the quality of teacher performance in learning. ABSTRAKKegiatan pendampingan Implementasi Kurikulum 2013 menjadi langkah awal yang sangat penting untuk mempercepat pemahaman dan keterampilan dalam mengimplementasikan kurikulum tersebut. Untuk memelihara dan meningkatkan kesinambungan, pemahaman dan implementasi kurikulum 2013 pada di masing-masing satuan pendidikan, dilaksanakan penelitian tentang pendampingan implementasi kurikulum 2013 melalui “Sulastri” pada SMPN 15 Banjarmasin. Program pendampingan ini dilakukan sebagai penguatan dalam memahami konsep kurikulum 2013.                Siklus I Perencanaan terdiri dari: a) Menetapkkan data guru yang akan diSulastri, b) Menyiapkan lembar observasi dalam bentuk instrumen Sulastri, yaitu instrumen supervisi administrasi KBM dan instrumen supervisi kelas, c) Mengadakan temu awal dengan para guru yang akan di Sulastri dalam rangka informasi dan penyusunan jadwal pada masing-masing Guru, d). Menyampaikan instrumen supervisi kepada masing-masing guru yang akan disupervisi, e) Menjelaskan penilaian yang perlu diketahui oleh guru yang terdapat dalam instrumen supervisi, f) Menjelaskan komponen perangkat utama administrasi pembelajaran yang dikumpulkan pada saat sebelum pelaksanaan supervisi kelas. Pada siklus II dilakukan apabila hasil siklus I dianggap belum berhasil atau indikator keberhasilan penelitian belum mencapai target yang telah ditetapkan.                 Dari pelaksanaan siklus I yang diterapkan dimana dilakukan Sulastri terhadap 14 orang guru telah terdapat peningkatan kualitas kinerja walaupun masih dalam tahaf awal, yang hasilnya adalah sebagai berikut:Hasil supervisi administrasi pembelajaran (administrasi KBM) pencapaian kualitas kinerja baik dan sangat baik sebesar 41,67%.Hasil supervisi kelas, pencapaian kualitas kinerja baik dan sangat baik sebesar 58,33%. Pelaksanaan siklus II yang diterapkan kembali dilakukan kegiatan Sulastri terhadap 14 orang guru sebagai subyek penelitian telah terdapat peningkatan kualitas kinerja yang sangat berarti, yaitu: 1) Hasil supervisi administrasi pembelajaran (perencanaan pembelajaran) pencapaian kualitas kinerja baik dan sangat baik sebesar 100%. 2) Hasil supervisi kelas (pelaksanaan pembelajaran), pencapaian kualitas kinerja baik dan sangat baik sebesar 92,85%.                Dengan supervisi berkesinambungan yang diterapkan pada semua guru minimal setahun sekali, maka guru dalam melaksanakan tugasnya dengan baik, karena mereka merasa adanya pengawasan/kontrol sekaligus pembinaan, sehingga dapat digunakan untuk mengukur kualitas kinerja guru pada kompetensi profesional baik aspek perencanaan pembelajaran maupun pelaksanaan pembelajarannya adalah dengan menerapkan strategi supervisi kelas terintegrasi disingkat Sulastri, dan dengan Melalui Sulastri ternyata dapat memotivasi tumbuhnya kemauan dan kemampuan untuk berubah yang berujung pada perubahan peningkatan kualitas kinerja guru dalam pembelajaran. Kata Kunci: Pendampingan Implementasi Kurikulum 2013, Melalui Sulastri.